Calcaneal reconstruction after total calcanectomy with iliac crest free flap. Issue 8 (22nd March 2019) - Innocenti, Marco; Lucattelli, Elena; Daolio, Primo Andrea; Bastoni, Stefano; Marini, Eleonora; Scoccianti, Guido; Menichini, Giulio
Abstract : Introduction: Calcaneal tumors being a rare occurrence, surgical options and outcomes are not well‐known. Extensive defects following wide resection, especially in weight‐bearing areas, still remain a challenge and different reconstructive techniques have been proposed. The aim of this report was to analyze the clinical and functional long‐term outcomes of heel reconstruction using an iliac crest free flap. Patients and methods: Four patients who underwent calcaneal reconstruction between 1999 and 2012 were included. Two were females and mean age was 27 years, ranging 18–42 years. Each patient underwent total calcanectomy, for two osteoblastomas, one osteosarcoma, and one Ewing's sarcoma. An iliac crest flap was harvested and shaped to fit the residual space. After the articular cartilage at recipient site was debrided, the flap was fixed to the talus and the cuboid. Results: The average size of the flaps was 2 x 7 x 5 cm. Postoperatively wound dehiscence, screw breaking, and graft fracture healed conservatively. All the arthrodesis healed successfully and no donor site complication occurred. At an average follow‐up of 13 years (range 6–19 years) any patient claimed pain, evident limp or limitation of daily activities. Computerized pedobarographic examination and gait analysis revealed a satisfactory result and an acceptable weight‐bearing area in the reconstructed limb in each patient. Conclusions: Calcaneal reconstruction with iliac crest free flap is likely to provide good chances of a long‐lasting result, especially in young patients. Particularly, it provides the possibility to adequately shape the graft to fit the bone loss while using the crest as the weight‐bearing surface.